Analysis of veldfire incidents in Makoni and Chimanimani districts of Zimbabwe using GIS, Remote Sensing and Public Domain data - Chigurah, Charles; Jerie, Steven (Clarion University, 2016)
This study examines the application of public domain data and remote sensing using the Moderate-Resolution Imaging Spectrometer (MODIS) instrument in the detection and monitoring of fire incidents in Zimbabwe with particular reference to Chimanimani and Makoni districts of Manicaland Province. The assessment, mapping, and analysis of the fire incidents were undertaken done using the Arc View Geographical Information Systems software with spatial analysis and extensions. The study revealed that in 2005, a total of 1,436 fire incidents were detected in the two districts, with 159 in the communal areas and the rest in the arms and exotic forest plantations. In 2006, the number of fire incidents declined to 490. The majority of the fires were detected in August and September due to the lack of rainfall during these months and the high summer temperatures that provide the suitable conditions for ignition. It is recommended that there is a need to develop a framework for the integration of GIS, Remote Sensing, and Public Domain data in veld-fire assessment.